Palladium-Catalyzed Direct C-H Arylation of 3-(Methylsulfinyl)thiophenes - Jiang, Hui (2018)
A palladium-catalyzed direct arylation of (3-thiophene)S(O)Me derivatives has been developed. This protocol is effective for the selective synthesis of 2-arylated and 2,5-diarylated sulfinylthiophene derivatives with as low as 0.5 mol % catalyst loading. Various functional groups are well tolerated. A method to install two different aryl groups on 3-(methylsulfinyl)thiophenes is also introduced.